A qualitative evaluation of coproduction of research: 'If you do it properly, you will get turbulence'. (5th May 2021) - Worsley, Joanne Deborah; McKeown, Mick; Wilson, Timothy; Corcoran, Rhiannon
Abstract: Background: Patients and public members are increasingly involved across the different stages of the research process. Their involvement is particularly important in the conception and design of applied health research where it enables people with lived experience to influence the aims, content, focus and methods. Objective: To evaluate the process of coproducing a mental health–related research proposal suitable for funding through a national health research funding body. Methods: Reflections from members of the public (n = 3) and academic researchers (n = 3) were collected through semi‐structured interviews. Data were thematically analysed. Results: Thematic analysis identified five overarching themes: valuing the lived experience perspective; matching ambitions to the funded research process; 'Us and them': power, relationships and trust; challenges; and benefits of coproduction. Conclusions: Our findings suggest that for successful coproduction of a research funding application, an open and trusting atmosphere, where equal relationships are established and a shared common goal agreed is essential. Although relationships with research professionals were framed by trust and mutual respect for some public advisors, others felt a sense of 'us and them'. With various tensions played out through interpersonal conflict, difficult conversations and disagreements, coproduction was not a positive experience for all stakeholders involved. Among the learning was that when collaboration of this kind is constrained by time or funding, genuine, impactful coproduction can be more challenging than is generally acknowledged.